Kajian Teks Ulasan Siswa Kelas VIIIB Di SMP N 3 Colomadu Tahun Pelajaran 2015/2016 - JAKA PURNOMO, ARIF; , Drs. Yakub Nasucha. M. Hum (2016)
The purpose of this study was to describe the identification of the structure of the review text VIIIB grade students of SMP N 3 Colomadu and to describe the study of texts in the review text VIIIB grade students of SMP N 3 Colomadu. The research is a qualitative descriptive case study research strategy rooted and a single case study. The data in this study is the text review VIIIB grade students of SMP N 3 Colomadu. Data collection techniques in this study using techniques and techniques refer to the note. The validity of the data in this study using triangulation theory. Data were analyzed using data reduction method. For in-depth understanding of the review text, then students need to gain an understanding of the structure of the review text and linguistic elements. Because both of these is a requirement to provide the study to a work primarily text-based works of text structure is part of building a text, so that it becomes an integral text. Structure in the review text include orientation, interpretation, evaluation and summary. In the study of texts has elements in it. The element is the content of text and language. Text language in the review are: Adjectives attitude, verbs, nouns, reference, spelling, diction. Text is an 2 important part of learning, especially Indonesian. Review text material given to help students recognize and realize the importance of giving an overview of a literary work, the suitability of the use of the structure as well as the language contained in the text, it can be expected student learning achieved.